Security technologies for the World Wide Web - Oppliger, Rolf (Artech House computer security series., 2000)
"This hands-on book gives you a comprehensive analysis of current trends in WWW security, plus an evaluation of existing technologies, such as anonymity services and security products. It helps you guarantee that electronic commerce applications on your website are executed with the utmost security and protection. What's more, it helps you understand content protection and the benefits and drawbacks of censorship on the web."--BOOK JACKET. "Geared toward proactive Internet security professionals, this handy resource helps you comprehend existing security technologies, evaluate and choose those that best suit your needs, understand corresponding software and hardware, and more."--Jacket